A new specimen of Plesiopterys wildi reveals the diversification of cryptoclidian precursors and possible endemism within European Early Jurassic plesiosaur assemblages - Marx,Miguel; Sachs,Sven; Kear,Benjamin P.; Eriksson,Mats E.; Nilkens,Klaus; Lindgren,Johan (PeerJ, 2025)
Background A virtually complete and articulated plesiosaur skeleton (MH 7) is described from the Lower Jurassic (Toarcian) Posidonienschiefer Formation near Holzmaden in southern Germany. Plesiosaur remains are rare in this rock unit compared to those of other marine reptiles, such as ichthyosaurs and thalattosuchian crocodylomorphs. The new specimen offers an opportunity to assess the biodiversity of Early Jurassic plesiosaurs documented from what is now Central Europe. Methods The osteology of MH 7 is described and compared with other Early Jurassic plesiosaurs based on first-hand observations. Phylogenetic analyses using both equal weighting and weighted parsimony determined phylogenetic placement within Plesiosauria. Results Plesiopterys wildi is an early-diverging plesiosauroid and a sister taxon to Franconiasaurus brevispinus and Cryptoclidia. MH 7 represents a subadult individual, providing an updated character state diagnosis of Plesiopterys wildi, which has hitherto only been known from the osteologically immature holotype SMNS 16812. The presence of multiple regionally distinct plesiosaur genera and species within the European epicontinental marine basins suggests possible paleobiogeographical segregation during the Toarcian.
Keywords: Biodiversity; Diversification; Endemism; Jurassic; Plesiosaur